An argument for ethical physical geography research on Indigenous landscapes in Canada. (2nd June 2014) - Kershaw, Geoffrey G. L.; Castleden, Heather; Laroque, Colin P.
Abstract In Canadian physical geography, the ethical implications of research occurring in Indigenous spaces and places have historically been overlooked. Physical geographers, particularly those working in northern Canada, are beginning to recognize that our research takes place in a sensitive social space and the knowledge we pursue has ethical and moral implications. The Canadian Geographer recently published a special issue (56:2) that documents the many challenges and opportunities of community‐based participatory research involving Indigenous peoples in Canada. Throughout that issue, the 2010 Tri‐Council Policy Statement, Ethical Conduct for Research Involving Humans (TCPS2), was referenced as important in directing a shift towards ethical interactions with Indigenous peoples in research. Drawing on material from the special issue and the TCPS2, this article gives an overview of the authors' experiences in attempting to execute an ethically sound physical geography study in traditional Dene territory in northern Saskatchewan. The viewpoint concludes with thoughts on what bridges and barriers exist when attempting physical geography research that is sensitive to the ethical responsibilities of working in Indigenous spaces. From our perspective, physical geographers can strengthen the ethical defensibility and overall quality of their research by enhancing involvement with indigenous communities that are potentially impacted by their research findings.